Legal Accountability and Governance in Corporate Social Responsibility Implementation in Indonesia - SETIAWAN, Armand; RIDENG, I Wayan; ARJAYA, I Made (Protection: Journal Of Land And Environmental Law, 2026)
This study aims to examine the legal accountability and governance dimensions of Corporate Social Responsibility (CSR) implementation in Indonesia. It addresses the issue of weak integration between CSR legal mandates and their practical realization within corporate governance frameworks. Using a normative juridical method with statutory and conceptual approaches, this research analyzes legal materials including Law No. 40 of 2007 on Limited Liability Companies and Government Regulation No. 47 of 2012 on Social and Environmental Responsibility, complemented by secondary literature and qualitative analysis. The findings indicate that CSR in Indonesia remains largely voluntary and philanthropic, with weak legal enforcement and limited standardized mechanisms for auditing and reporting. The absence of clear sanctions for non-compliance and the lack of transparency hinder CSR’s potential to function as a governance instrument that ensures corporate accountability. The study interprets CSR as a legally binding element of corporate governance that strengthens ethical responsibility, transparency, and stakeholder trust. It concludes that reinforcing CSR enforcement through standardized reporting, independent auditing, and regulatory collaboration can transform CSR from a symbolic practice into a binding social commitment that supports sustainable national development.